Effect of inlet section on pulse combustor performance - Abdul Wahid, Mazlan (Buang Hatta University, 2008)
Experimental investigation on a valveless pulse combustor that applies Helmholtz resonation concepts is presented. The pulse combustor is attached with a J-shape inlet. Part of the burnt gases mixes with inlet air in the J-shape inlet due to pulse action. Since the J-shape is in the same direction as the tailpipe, it also produces additional thrust. The thrust produced is from 22.07 N to 31.88 N. The J-shape inlet increases the minimum required fuel supply. It also reduces the noise that is produced by the pulse combustor. It is shown that the optimum range of fuel supply for the pulse combustor is in the lean region. The effect of the J-shape inlet to the operating frequency is the same as lengthening the tail pipe with a frequency of 125 Hz with the J-shape and 157 Hz without